A striking colony morphotype of Aplidium proliferum (Milne Edwards, 1841) (Ascidiacea: Polyclinidae) from the Strait of Gibraltar. - A. RAMOS-ESPLA; O. OCAÑA (Mediterranean Marine Science, 2017)
An unusual colonial ascidian with 1-2m in length, belonging to the genus Aplidium (Ascidiacea: Polyclinidae), has been sampled from the Strait of Gibraltar (Ras Leona, Morocco). The characteristics of the colony, zooids and larvae point us to A. proliferum. The species seems common in the NE Atlantic from the Shetland Islands to Mediterranean Sea, but it never has observed the size of colonies as found in this area, the Strait is the largest so far reported, which it is probably represents one of the longest ascidian worldwide.

Alien species in the Mediterranean Sea by 2012. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part 2. Introduction trends and pathways - Α. ZENETOS; S. GOFAS; C. MORRI; A. ROSSO; D. VIOLANTI; J.E. GARCIA RASO; M.E. CINAR; A. ALMOGI-LABIN; A.S. ATES; E. AZZURRO; E. BALLESTEROS; C.N. BIANCHI; et al. (Mediterranean Marine Science, 2012)
More than 60 marine non-indigenous species (NIS) have been removed from previous lists and 84 species have been added, bringing the total to 986 alien species in the Mediterranean [775 in the eastern Mediterranean (EMED), 249 in the central Mediterranean (CMED), 190 in the Adriatic Sea (ADRIA) and 308 in the western Mediterranean (WMED)]. There were 48 new entries since 2011 which can be interpreted as approximately one new entry every two weeks. The number of alien species continues to increase, by 2-3 species per year for macrophytes, molluscs and polychaetes, 3-4 species per year for crustaceans, and 6 species per year for fish. The dominant group among alien species is molluscs (with 215 species), followed by crustaceans (159) and polychaetes (132). Macrophytes are the leading group of NIS in the ADRIA and the WMED, reaching 26-30% of all aliens, whereas in the EMED they barely constitute 10% of the introductions. In the EMED, molluscs are the most species-rich group, followed by crustaceans, fish and polychaetes. More than half (54%) of the marine alien species in the Mediterranean were probably introduced by corridors (mainly Suez). Shipping is blamed directly for the introduction of only 12 species, whereas it is assumed to be the most likely pathway of introduction (via ballasts or fouling) of another 300 species. For approximately 100 species shipping is a probable pathway along with the Suez Canal and/or aquaculture. Approximately 20 species have been introduced with certainty via aquaculture, while >50 species (mostly macroalgae), occurring in the vicinity of oyster farms, are assumed to be introduced accidentally as contaminants of imported species. A total of 18 species are assumed to have been introduced by the aquarium trade. Lessepsian species decline westwards, while the reverse pattern is evident for ship-mediated species and for those introduced with aquaculture. There is an increasing trend in new introductions via the Suez Canal and via shipping.

New Mediterranean Biodiversity Records (December 2012) - M. THESSALOU-LEGAKI; O. AYDOGAN; P. BEKAS; G. BILGE; Y.O. BOYACI; E. BRUNELLI; V. CIRCOSTA; F. CROCETTA; F. DURUCAN; M. ERDEM; A. ERGOLAVOU; H. FILIZ; et al. (Mediterranean Marine Science, 2012)
This paper presents records extending or confirming the distribution of Mediterranean species. Three alien algae are included, namely Codium taylorii reported for the first time from the Aegean and Turkey (Izmir Gulf), Caulerpa racemosa var. cylindracea (Karpathos and Chalki Isl., Aegean Sea) and Ganonema farinosum (Karpathos Isl., Aegean Sea). As far as animals are concerned, Litarachna divergens (Acari: Hydrachnidia) was recorded (Side, Eastern Mediterranean) and represents a new amendment at genus level for Turkish fauna. Other invertebrates include alien species such as the crabs Dyspanopeus sayi (Lago Fusaro, SW Italy), Percnon gibbesi (Larnaca, Cyprus; Karpathos and Chalki Isl., Aegean Sea) and Callinectes sapidus (Voda estuary, NW Greece), the nudibranch Aplysia dactylomela (Boka Kotorska Bay, Montenegro), the gastropod Conomurex persicus (Karpathos and ChalkiIsl., Aegean Sea) and the bryozoan Electra tenella (Livorno harbour and Messina Straits area). The alien fish Siganus luridus, Siganus rivulatus, Fistularia commersonii, Sphyraena chrysotaenia and Sargocentron rubrum are also reported from the islands of Karpathos and Chalki, and Pteragogus pelycus from Heraklion Bay, Crete. In addition, new localities for four rare Mediterranean inhabitants are given: the cephalopod Thysanoteuthis rhombus (NW Sardinia) and the fish: Lampris guttatus (Calabria, S Italy), Petromyzon marinus (Gokova Bay) and Remora australis (Saronikos Gulf), while the opisthobranch gastropod Cerberilla bernadettae is reported for the first time from the E Mediterranean (Cyprus). Finally, three species of the Aegean ascidiofauna are recorded for the first time: Lissoclinum perforatum, Ciona roulei and Ecteinascidia turbinata. Furthermore, it was established that Phallusia nigra has extended its distributional range to the north of the Aegean Sea.

New Mediterranean Biodiversity Records (June 2012) - A. NICOLAIDOU; G. ALONGI; O. AYDOGAN; M. CATRA; L. CAVAS; C. CEVIK; A. DOSI; V. CIRCOSTA; S. GIAKOUMI; F. GIMENEZ-CASALDUERO; H. FILIZ; A. IZQUIERDO-MUNOZ; et al. (Mediterranean Marine Science, 2012)
The present work reports on the extended distribution of nineteen species in the Mediterranean. These are: Upeneus pori(Fish:Turkey), Bursatella leachii (Mollusca, Opisthobranchia: eastern coast of Spain), Sparisoma cretense (Fish: Ionian coastof Greece), Pseudobryopsis myura (Chlorophyta: Turkey), Aplysia dactylomela (Mollusca, Opisthobranchia: Karpathos island,and Kyklades Archipelago, Greece), Asparagopsis armata and Botryocladia madagascariensis (Rhodophyta: South Peloponnesos,Greece), Oxynotus centrina (Fish: Greece), Caulerpa racemosa var. cylindracea (Chlorophyta ), Stypopodium schimperi(Phaeophyta ) Siganus luridus and Stephanolepis diaspros (Fish) Percnon gibbesi (Decapoda, Brachyura) (Kyklades Archipelago,Greece), Cerithium scabridum (Mollusca, Prosobranchia: Anavissos: Greece) and Cerithium renovatum (Mollusca, Prosobranchia:N. Κriti), Cassiopea andromeda (Scyphomedusa: Rhodos Island, Greece), Abra tenuis (Mollusca Bivalvia: VouliagmeniLake, Greece) Lagocephalus lagocephalus (Fish: Calabrian coast, Italy) and Plocamopherus ocellatus (Mollusca, Opisthobranchia:İskenderun Bay, Turkey).

Spatial distribution and abundance of the megabenthic fauna community in Gabes gulf (Tunisia, eastern Mediterranean Sea) - H. EL LAKHRACH; A. HATTOUR; O. JARBOUI; K. ELHASNI; A.A. RAMOS-ESPLA (Mediterranean Marine Science, 2012)
The aim of this paper is to bring to light the knowledge of marine diversity of invertebrates in Gabes gulf. The spatial distribution of the megabenthic fauna community in Gabes gulf (Tunisia, Eastern Mediterranean Sea), together with the bottom type and vegetation cover, were studied. The abundance of the megabenthic fauna was represented by eight groups: Echinodermata (38%), Crustacea (21%), Tunicata (19%), Mollusca (13%), Porifera (4%), Cnidaria (3%), Bryozoa, and Annelida (2%). It was spatially more concentrated in the coast area of the gulf than in the offshore waters. This area, especially, in Southern Kerkennah, North-est of Gabes and North-east of Djerba appeared to be in a good ecological condition hosting a variety of species like the paguridsPaguristes eremita and Pagurus cuanensis, the brachyura Medorippe lanata, Inachus doresttensis, the Gastropoda Hexaplex trunculus, Bolinus brandaris, Aporrhais pespelecani, andErosaria turdus, the Bivalvia Fulvia fragilis, the Echinoidea Psammechinus microtuberculatus, Holothuria polii,Ophiothrix fragilis and Antedon mediterranea, and the AscidiaceaAplidium cf. conicum, Didemnum spp, and Microcosmus exasperatus.The species’ compositions of the megabentic fauna community showed clearly that the spatial analysis represented the differences between the community of these two regions (inshore waters and offshore waters). These differences were closely related to peculiar characters of the fauna and biotopes (depth, bottom type and vegetation cover community). The results of the present study should be considered as a necessary starting point for a further analysis of priceless benthic fauna contribution to the marine environment and its organisms.

Errata to the Review Article (Medit. Mar. Sci. 11/2, 2010, 381-493): "Alien species in the Mediterranean Sea by 2010. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part I. Spatial distribution" - A. ZENETOS; S. GOFAS; M. VERLAQUE; M.E. CINAR; J.E GARCIA RASO; C.N. BIANCHI; C. MORRI; E. AZZURRO; M. BILECENOGLU; C. FROGLIA; I. SIOKOU; D. VIOLANTI; et al. (Mediterranean Marine Science, 2011)
The state-of-art on alien species in the Mediterranean Sea is presented, making distinctions among the four subregions defined in the EU Marine Strategy Framework Directive: (i) the Western Mediterranean Sea (WMED); (ii) the Central Mediterranean Sea (CMED); (iii) the Adriatic Sea (ADRIA); and (iv) the Eastern Mediterranean Sea (EMED). The updated checklist (December 2010) of marine alien species within each subregion, along with their acclimatization status and origin, is provided. A total of 955 alien species is known in the Mediterranean, the vast majority of them having being introduced in the EMED (718), less in the WMED (328) and CMED (267) and least in the Adriatic (171). Of these, 535 species (56%) are established in at least one area.Despite the collective effort of experts who attempted in this work, the number of introduced species remains probably underestimated. Excluding microalgae, for which knowledge is still insufficient, aliens have increased the total species richness of the Mediterranean Sea by 5.9%. This figure should not be directly read as an indication of higher biodiversity, as spreading of so many aliens within the basin is possibly causing biotic homogenization. Thermophilic species, i.e. Indo-Pacific, Indian Ocean, Red Sea, Tropical Atlantic, Tropical Pacific, and circum(sub)tropical, account for 88.4% of the introduced species in the EMED, 72.8% in the CMED, 59.3% in the WMED and 56.1% in the Adriatic. Cold water species, i.e. circumboreal, N Atlantic, and N Pacific, make up a small percentage of the introduced species, ranging between 4.2% and 21.6% and being more numerous in the Adriatic and less so in the EMED.Species that are classified as invasive or potentially invasive are 134 in the whole of the Mediterranean: 108 are present in the EMED, 76 in the CMED, 53 in the Adriatic and 64 in the WMED. The WMED hosts most invasive macrophytes, whereas the EMED has the lion’s share in polychaetes, crustaceans, molluscs and fish.

Alien species in the Mediterranean Sea by 2010. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part I. Spatial distribution - A. ZENETOS; S. GOFAS; M. VERLAQUE; M.E. CINAR; J.E. GARCIA RASO; C.N. BIANCHI; C. MORRI; E. AZZURRO; M. BILECENOGLU; C. FROGLIA; I. SIOKOU; D. VIOLANTI; et al. (Mediterranean Marine Science, 2010)
The state-of-art on alien species in the Mediterranean Sea is presented, making distinctions among the four subregions defined in the EU Marine Strategy Framework Directive: (i) the Western Mediterranean Sea (WMED); (ii) the Central Mediterranean Sea (CMED); (iii) the Adriatic Sea (ADRIA); and (iv) the Eastern Mediterranean Sea (EMED). The updated checklist (December 2010) of marine alien species within each subregion, along with their acclimatization status and origin, is provided. A total of 955 alien species is known in the Mediterranean, the vast majority of them having being introduced in the EMED (718), less in the WMED (328) and CMED (267) and least in the Adriatic (171). Of these, 535 species (56%) are established in at least one area.Despite the collective effort of experts who attempted in this work, the number of introduced species remains probably underestimated. Excluding microalgae, for which knowledge is still insufficient, aliens have increased the total species richness of the Mediterranean Sea by 5.9%. This figure should not be directly read as an indication of higher biodiversity, as spreading of so many aliens within the basin is possibly causing biotic homogenization. Thermophilic species, i.e. Indo-Pacific, Indian Ocean, Red Sea, Tropical Atlantic, Tropical Pacific, and circum(sub)tropical, account for 88.4% of the introduced species in the EMED, 72.8% in the CMED, 59.3% in the WMED and 56.1% in the Adriatic. Cold water species, i.e. circumboreal, N Atlantic, and N Pacific, make up a small percentage of the introduced species, ranging between 4.2% and 21.6% and being more numerous in the Adriatic and less so in the EMED.Species that are classified as invasive or potentially invasive are 134 in the whole of the Mediterranean: 108 are present in the EMED, 76 in the CMED, 53 in the Adriatic and 64 in the WMED. The WMED hosts most invasive macrophytes, whereas the EMED has the lion’s share in polychaetes, crustaceans, molluscs and fish.

Chemical defenses of tunicates of the genus Aplidium from the Weddell Sea (Antarctica) - L. Núñez-Pons; R. Forestieri; R. M. Nieto; M. Varela; M. Nappo; J. Rodríguez; C. Jiménez; F. Castelluccio; M. Carbone; A. Ramos-Espla; M. Gavagnin; C. Avila (Polar Biology, 2010)

Trace elements in otoliths of the two‐banded bream from a coastal region in the south‐west Mediterranean: are there differences among locations? - B. M. Gillanders; P. Sanchez‐Jerez; J. Bayle‐Sempere; A. Ramos‐Espla (Journal of Fish Biology, 2001)
There were no significant differences in otolith chemistry (Li, Mn, Sr, Cd, Ba) of Diplodus vulgaris between sites (distances >100 m) and few differences among locations (distance >10 km) along the south‐west coast of Spain. Multivariate analysis of otolith chemistry detected a difference among locations, but a posteriori comparisons could not detect which locations differed. This is one of the few studies to show little variation in otolith chemistry among locations. Of the studies reviewed,